The Overlord protocol - Walden, Mark (Walden, Mark. H.I.V.E., 2008)
Still trapped at the Higher Institute of Villainous Education, or H.I.V.E., evil-genius-in-training Otto Malpense is nearly assassinated and must now not only try to escape, but also find out who murdered his best friend--and save himself.